To subtract the expression \( 12(z+4) - 3(14z+1) \), we will follow the steps of distributing and then combining like terms.
-
Distribute:
\[ 12(z + 4) = 12z + 48 \]
\[ -3(14z + 1) = -42z - 3 \]
-
Combine the results:
Now we combine the two results we calculated.
\[ 12z + 48 - 42z - 3 \]
-
Combine like terms:
For \( z \):
\[ 12z - 42z = -30z \]
For the constants:
\[ 48 - 3 = 45 \]
-
Final result:
Putting it all together, we have:
\[ -30z + 45 \]
Thus, the final result is:
\[ \boxed{-30z + 45} \]